2017
DOI: 10.21273/hortsci11248-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Nano-nitrogen and Urea Fertilizers on the Physical and Chemical Properties of Pomegranate (Punica granatum cv. Ardestani) Fruits

Abstract: The aim of this study was to compare the effects of foliar fertilization with a nitrogen (N) fertilizer containing nanoparticles (nN) with those of foliar fertilization with urea on the characteristics of pomegranate fruits cv. Ardestani. The experiment was carried out using a completely randomized block design with five treatments and four replications (trees) per treatment during two consecutive years, 2014 and 2015. Two foliar applications of nN (0.25 and 0.50 g N/L, equivalent to ≈1.3 and 2.7 g N/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
13
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 39 publications
10
13
1
1
Order By: Relevance
“…Nano urea interestingly increased essential oil production. Davarpanah et. al., (2017) indicated that the two foliar applications of nN (0.25 and 0.50 g N/L, equivalent to '1.3 and 2.7 g N/tree or 0.9 and 1.8 kg N/ha; nN1 and nN2, respectively) and urea (4.6 and 9.2 g N/L, equivalent to '24.4 and 48.8 g N/tree or 16.3 and 32.5 kg N/ha; U1 and U2, respectively) were applied at full bloom and 1 month later.…”
Section: Introductionmentioning
confidence: 99%
“…Nano urea interestingly increased essential oil production. Davarpanah et. al., (2017) indicated that the two foliar applications of nN (0.25 and 0.50 g N/L, equivalent to '1.3 and 2.7 g N/tree or 0.9 and 1.8 kg N/ha; nN1 and nN2, respectively) and urea (4.6 and 9.2 g N/L, equivalent to '24.4 and 48.8 g N/tree or 16.3 and 32.5 kg N/ha; U1 and U2, respectively) were applied at full bloom and 1 month later.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study also indicated that the increase in phenolic components was due to an increase in the expression of genes coding for the biosynthesis of phenolic compounds induced by Zn and B . Treatment with N‐containing NFs at 0.25 (N1) and 0.50 (N2) g L −1 also improved the quality of pomegranate fruits by increasing aril juice (mL 100 g −1 arils) (control: 62.5; N1: 63.3; N2: 68.3), total sugars (g 100 g −1 juice) (control: 14.18; N1: 14.56; N2: 15.54) and TA (%) (control: 1.74; N1: 1.84; N2: 1.89) of fruits . An increase in N concentration improved turgor pressure, carbohydrate supply and translocation of organic acids .…”
Section: Can Nps Enhance the Yield Of Fruit Trees?mentioning
confidence: 81%
“…Spraying NMs and nanocomposites containing essential macronutrients and micronutrients had positive effects on the fertilization and production of fruits in several fruit trees.…”
Section: Can Nps Enhance the Yield Of Fruit Trees?mentioning
confidence: 99%
See 2 more Smart Citations